Real-world treatment and outcomes of ALK-positive metastatic non–small cell lung cancer in a southeast Asian country - Poh, Mau Ern; How, Soon Hin; Ho, Gwo Fuang; Pang, Yong Kek; Hasbullah, Harissa H; Tho, Lye Mun; Muhamad Nor, Ibtisam; Lim, Bee Chiu Lim; Ho, Kean Fatt; Thiagarajan, Muthukkumaran; Samsudin, Azlina; Omar, Azza; et al. (Dove Medical Press, 2023)
Purpose: Anaplastic lymphoma kinase (ALK) inhibitors are associated with good overall survival (OS) for ALK-positive metastatic non–small cell lung cancer (NSCLC). However, these treatments can be unavailable or limited by financial constraints in developing countries. Using data from a nationwide lung cancer registry, the present study aimed to identify treatment patterns and clinical outcomes of ALK-positive NSCLC in Malaysia. Methods: This retrospective study examined data of patients with ALK-positive NSCLC from 18 major hospitals (public, private, or university teaching hospitals) throughout Malaysia between January 1, 2015 and December 31, 2020 from the National Cardiovascular and Thoracic Surgical Database (NCTSD). Data on baseline characteristics, treatments, radiological findings, and pathological findings were collected. Overall survival (OS) and time on treatment (TOT) were calculated using the Kaplan–Meier method. Results: There were 1581 NSCLC patients in the NCTSD. Based on ALK gene-rearrangement test results, only 65 patients (4.1%) had ALK-positive advanced NSCLC. Of these 65 patients, 59 received standard-of-care treatment and were included in the analysis. Crizotinib was the most commonly prescribed ALK inhibitor, followed by alectinib and ceritinib. Patients on ALK inhibitors had better median OS (62 months for first-generation inhibitors, not reached at time of analysis for second-generation inhibitors) compared to chemotherapy (27 months), but this was not statistically significant (P=0.835) due to sample-size limitations. Patients who received ALK inhibitors as first-line therapy had significantly longer TOT (median of 11 months for first-generation inhibitors, not reached for second-generation inhibitors at the time of analysis) compared to chemotherapy (median of 2 months; P<0.01). Conclusion: Patients on ALK inhibitors had longer median OS and significantly longer TOT compared to chemotherapy, suggesting long-term benefit. Keywords: ALK inhibitors, chemotherapy, ALK-positive, NSCLC